REBT Module Development in Pastoral Counseling Service for PLHA in Maluku Protestant Church - Andris Noya; Franklin Untailawan (SOSHUM : Jurnal Sosial dan Humaniora, 2022)
HIV (Human Immunodeficiency Virus) and AIDS (Acquired Immunodeficiency Syndrome) are global pandemics that draw the world's attention. Since 1987, the cases of HIV/AIDS have been declared as a humanitarian crisis and have become a challenge to the development and progress of Indonesia. In addition, as a province with a relatively large number of cases, handling HIV/AIDS is certainly a concern for the government and the church community in Maluku. In the process of pastoral counseling service by Maluku Protestants Church (GPM), the spiritual assistance to the People Living with HIV/AIDS (PLHA) is going well. Even so, they didn’t have guidance from a psychological perspective such as therapy or other methods to strengthen the assistance. To this concern, this study aims to develop a module of Rational Emotive Behavior Therapy (REBT) in pastoral counseling service for PLHA in Maluku Protestants Church. The method used in the study was a Research and Development with ADDIE Model. There are five procedural stages of developing the module based on this model namely, analysis, design, development, implementation and evaluation. The subject in the study were the servants of pastoral counseling in the Maluku Protestants Church who are spread in three service areas such as in Masohi City and Lease Islands (in Central Maluku Regency) and Ambon City (the capital of Maluku). The results conclude that the REBT module is effective for the pastoral counseling service to the PLHA in Maluku Protestants Church.